Assessment of socio-economic policy in the field of socio-economic security based on an analysis of the state of security of lower Silesia. (18th August 2020) - Popławski, Maciej
ABSTRACT: This article objective is to present an assessment of the socio-economic policy pursued by the authorities in the field of socio-economic security in Lower Silesia. The assessment is a result of research and analysis conducted by the research team at the Faculty of Management of the Gen. T. Kościuszko Military University of Land Forces, Wrocław to design the "Multifactorial model of socio-economic security" . The project assumes that the factors of economic development and factors determining the standard of living (here understood as living conditions of the population) properly diagnosed can give a picture of the level of socio-economic security, and their forecast will help prevent future threats in specific areas of the social life of the analyzed area.